2001
DOI: 10.1073/pnas.98.3.1154
|View full text |Cite
|
Sign up to set email alerts
|

Activated Cdc42/Rac reconstitutes FcɛRI-mediated Ca2+mobilization and degranulation in mutant RBL mast cells

Abstract: Antigen stimulation of mast cells via FcRI, the high-affinity receptor for IgE, triggers a signaling cascade that requires Ca 2؉ mobilization for exocytosis of secretory granules during an allergic response. This study investigates critical signaling components by using mutant RBL mast cells that are defective in antigen-stimulated phospholipase C␥ (PLC␥) activation, as well as other signaling activities downstream of stimulated tyrosine phosphorylation. We show that the expression of activated versions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 27 publications
3
55
1
Order By: Relevance
“…The functional defects observed in mice deficient in PLC␥ 2 are not restricted to B cells but are also observed in platelets, natural killer cells, monocytes/macrophages, and mast cells (60,61 There was no effect, however, of activated Cdc42 on PLC␥ 1 activity upon reconstitution of the two purified proteins in a cell-free system (65). At first glance, these findings are not easily consistent with the findings reported here.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The functional defects observed in mice deficient in PLC␥ 2 are not restricted to B cells but are also observed in platelets, natural killer cells, monocytes/macrophages, and mast cells (60,61 There was no effect, however, of activated Cdc42 on PLC␥ 1 activity upon reconstitution of the two purified proteins in a cell-free system (65). At first glance, these findings are not easily consistent with the findings reported here.…”
Section: Discussioncontrasting
confidence: 55%
“…However, PLC␥ 2 was apparently not examined in the latter studies, and the results presented here do not exclude the possibility that activated Cdc42 and Rac1 interact with PLC␥ 1 and that Cdc42 interacts with PLC␥ 2 without enhancing the catalytic activities of the PLC␥ isozymes. Moreover, activated Cdc42 appeared to interact with a species of PLC␥ 1 that migrated slightly faster on SDS-polyacrylamide gels than the majority of recombinant PLC␥ 1 , suggesting that it may be a modified form of the enzyme that binds most effectively to activated Cdc42 (65).…”
Section: Discussionmentioning
confidence: 99%
“…Patch clamp studies have established that Rac and Cdc42 regulate the early calcium release-activated calcium current (I CRAC ) as well as receptor-mediated calcium influx [23]. Expression of constitutively active mutants of Rac and Cdc42 in B6A4C1 cells, which are deficient in the calcium response, reconstituted the early (1 min) calcium influx wave [22,43]. Taken together, these observations suggest that Rac and Cdc42 are most likely upstream of PLCc.…”
Section: Discussionmentioning
confidence: 55%
“…Studies in bone marrow mast cells derived from PKCd -/-mice showed that PKCd plays a negative role in calcium mobilization and antigen-induced mast cell degranulation [46]. Given that Rac and Cdc42 activation are required for calcium signaling in mast cells [21][22][23][24]43], the effects of PKCd on degranulation could be in part via inhibition of Rac. The mechanism for PKC-mediated inhibition of Rac is yet to be determined but could involve PKC regulation of a Rac-specific guanine nucleotide exchange factor (GEF) or GAP, analogous to the inhibition of Ral-GEF by PKC [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation